Urgensi Analisis Kebutuhan Peserta Didik terhadap Proses Pembelajaran - Rika Devianti; Suci Lia Sari (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2020)
The achievement of the quality of education departs from the quality of the school and the quality of the learning process that is effective and efficient. To achieve effective and efficient learning, it is inseparable from the efforts of teachers to understand, guide and fulfill the needs of students in schools. Fulfilling the needs of students is a motivation. Therefore, a teacher needs to understand, know the types and levels of needs of their students, so that they can guide and fulfill the needs of students through various learning activities so that teachers can provide lessons as precisely as possible in order to achieve educational goals and create quality education.